Exploring sustainability in fluorine methodologies - Morgan, Patrick (2022)
The fluorination of organic compounds is extremely important to the modern world, especially within the chemical sciences, however as we transition to a more sustainable future, current industrial fluorination methodologies grow increasingly unsuitable towards the preparation of these fluorinated molecules, especially from an energy and materials perspective. To address this new fluorination, defluorination and fluorine transfer methodologies have been developed with a focus on improved sustainability over traditional fluorination techniques.